Coordination Between Monetary and Fiscal Policies (Socio-Economic Development Panorama, 2009)
The challenges that Government faces regarding maintaining overall economic policy is to bring forth macroeconomic stability management. The article explores how interest rate, money and exchange rates are affixed towards balancing the economy so that it is properly nurtured, and stands the multifaceted tirades of economic instability climate.  It oversees to chalk out policy upon how the State, Banks and fiscal authorities can put into effort so as to help balance the economic management institutions.  It solicits measures upon how to overcome leakages, corruption, maintain fiscal discipline, increase domestic saving ratio, etc.It underlines steps to strategically carve into measures to harmonies expenditure thrust on general administration, economic service, social service and so defense, etc. that the fiscal and monetary policy functions effectively. This entails steps to incorporate a more people centered good governance climate. The article underlines how the Interim plan budget endeavors to focus on the prevailing economic situation of the country; and deal with minimizing the rate of influence and the creation of a balance between the economic and non-economic sectors by maintaining fiscal discipline. A well-conceived economic plan consists with the maintenance of a balanced equitable growth trajectory; whereby all the major economic players coalesce together, synthesize and collaborate to usher into monetary and fiscal transformation of the society.Key words: Monetary and fical policy; Nepal Rastra Bank; macro economy; interim plan; economic programSocio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June